APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING THE GERMAN LANGUAGE DURING DISTANCE EDUCATION - Vylinskyi, Sviatoslav (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to highlighting the theoretical and practical experience of using ICT in the process of learning German for students of higher education at the Educational and Scientific Institute of International Relations of Taras Shevchenko National University of Kyiv, specialty 291 "International Relations, Public Communications and Regional Studies". The purpose of the article is to investigate the role of modern information and communication technologies in the study of the German language by students of higher education major 291 "International relations, public communications and regional studies" of the Bachelor's degree during distance learning and to analyze the main forms of work organization using information and communication technologies . The focus is on practical means of using ICT in higher education German classes, such as video conferencing, audio recordings, social networks, multimedia presentations, computer programs, e-references, online dictionaries, virtual learning environments, blogs, online platforms for learning foreign languages, etc. The specifics of the selected online platforms for learning the German language, which allow for high-quality training of students of higher education institutions in the conditions of mixed and distance learning, are characterized. Attention is focused on the approach to continuous education, which provides an opportunity to develop the skills of self-education and research-research activities of higher education seekers and contributes to an effective educational process. It is proven that ICT increases the effectiveness of the educational process; help in finding new, non-traditional forms and methods of learning; contribute to high-quality monitoring of educational activities of students of higher education, as well as increasing interest in learning and motivation of students' educational activities, development of activity, independence and creative skills